(untitled) (Comprehensive Journal of Science, 2026)
The weir is important because it is a tool for measuring the water discharges (Q (L3 / T) flowing through the exposed channels, weir is an easy-to-use, economical tool. Uses of weirs in riverbeds, valleys, sewage treatment plants and dam projects, as well as used in hydraulic and fluid laboratories as models to measure the discharge of water channels. There are several types of weirs with different geometric shapes and functions. This research deals with a laboratory study to derive the behaviour coefficient equations (Cd) for two models of sharp-crested for v-notch weir (Ѳ= 60o) and rectangular weir. From the summary of the laboratory and theoretical experiments of these models. Two equations were concluded that link the relationships between the independent variables, and the discharge coefficient for both weirs. A strong relationship and agreement were found between the measured discharge coefficient (Cd me) and the estimated (Cd Pre) where the correlation coefficient for v-notch weir was(R2=0.98)and the rectangular notch weir (R2 = 1).